Sentencing Disparities for Small-Quantity Drug Users and Their Impact on Prison Overcrowding in Indonesia - Shania Vira Aisyah; Noenik Soekorini; Renda Aranggraeni; Dudik Djaja Sidharta (Penerbit Goodwood, 2026)
Purpose: This study analyzes sentencing disparities in narcotics cases involving drug users possessing small quantities of narcotics in Indonesian courts and examines their contribution to prison overcrowding.Research Methodology: This research employs a normative legal research design applying statutory, conceptual, case, and comparative approaches. Data were collected through systematic analysis of statutory regulations, published court decisions, Supreme Court Circular Letters, and peer-reviewed legal literature.Results: The analysis reveals significant sentencing disparities in comparable narcotics user cases, with courts inconsistently imposing imprisonment, suspended sentences, or rehabilitation orders despite substantially similar factual circumstances. The dominance of custodial sentences directly contributes to prison overcrowding.Conclusions: Sentencing inconsistency reflects weak standardization in narcotics law enforcement and inadequate implementation of rehabilitation policies, producing systemic overcrowding in correctional institutions. Reformulating sentencing guidelines and strengthening rehabilitation mechanisms are essential steps toward a more proportionate and consistent criminal justice system.Limitations: The study is limited by restricted access to comprehensive published court decisions and the absence of nationwide empirical correctional data.Contributions: This research contributes to criminal law policy reform by proposing a normative framework for rehabilitation-oriented sentencing and reducing disparities in narcotics cases.